2021
DOI: 10.1097/jom.0000000000002250
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and COVID-19 Related Stressors Among Healthcare Workers Who Performed Shift Work at Four COVID-19 Dedicated Hospitals in Korea

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In addition, participants appeared to have persistent fears of unintentional exposure and of transmitting the virus to co-workers [ 34 ]. Nurses who performed shift work during COVID-19 had a significantly increased association between COVID-19-related work stressors and anxiety disorder [ 24 ]. These physiological and psychological conditions are reported to create high stress and further lead to post-traumatic stress [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, participants appeared to have persistent fears of unintentional exposure and of transmitting the virus to co-workers [ 34 ]. Nurses who performed shift work during COVID-19 had a significantly increased association between COVID-19-related work stressors and anxiety disorder [ 24 ]. These physiological and psychological conditions are reported to create high stress and further lead to post-traumatic stress [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, since February 2020, COVID-19 hospitals have been designated and operated for safe isolation beds for hospitalization of COVID-19 patients [ 22 ]. As patients diagnosed with COVID-19 are transferred to a designated hospital, operating a medical system that receives intensive treatment and care, the nurses at the hospitals are facing a high level of depression, anxiety, and stress [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…This result agreed with a study that was carried out to assess anxiety and COVID-19 related stressors among nursing staff who performed shift work at four COVID-19 dedicated hospitals in Korea. The results of the study showed that the percentage of generalized anxiety disorder was 122 (32%) of the participating nurses, as most of them were females under the age of 50 years (Park, S., et al, 2021). Feingold, J.H., et al, (2021) conducted a study to assess the psychological impact on frontline nursing staff during the pandemic surge in New York City during the COVID-19 pandemic.…”
Section: Discussion the Descriptive Analysis Of Items Of Generalized ...mentioning
confidence: 99%
“…Shift work has numerous harmful effects on employees' health, which can be mentioned such as the effect on the circadian and sleep‐wake cycles, adverse effects on family and social life, and long‐term effects, including digestive and cardiovascular problems and the risk of neuropsychiatric diseases 6 . Shift workers, precisely women, are exposed to various mental problems, specifically depression symptoms 7,8 . The tendency to bad habits is more in jobs that are done at night.…”
Section: Introductionmentioning
confidence: 99%
“…6 Shift workers, precisely women, are exposed to various mental problems, specifically depression symptoms. 7,8 The tendency to bad habits is more in jobs that are done at night. Shift work can change the pattern of food consumption.…”
Section: Introductionmentioning
confidence: 99%